Knowledge About the Stages of Healthy Food Processing Among Micro-Entrepreneurs in Penajam Paser Utara Regency - Nurlianti Nurlianti; Irfansyah Baharuddin Pakki; Tetra Hidayati; Ratih Wirapuspita Wisnuwardani (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Food Safety is a very important knowledge to be applied to MSMEs, considering that potential irregularities in food processing and distribution can pose health risks to consumers and can harm these small business actors. Objective : This study aims to analyze the relationship between the level of knowledge and attitudes of Food Safety in Penajam Paser Utara Regency Research Methods/ Implementation Methods : The method used was descriptive with a cross sectional design involving 300 respondents selected by simple random sampling Results : Micro business owners with better knowledge of food safety tend to have more positive attitudes towards food safety, such as mask use and participation in early detection. In addition, the length of time running a business and education factors and influence the increase in knowledge and positive attitudes towards food safety. Conclusion/Lesson Learned : Based on these findings, it is recommended that a structured and sustainable Food Safety education program be improved, with wider involvement of MSMEs and the authority of the Health Office and Balai POM as resource persons to provide information that is easily understood by MSMEs when carrying out Food Safety Training activities. Thus, it is expected that food safety efforts can be more effective.